DEVELOPMENT OF DIGITAL COMIC AS A BIOLOGY LEARNING MEDIA - Monika Sari Dewi Damanik; Herbert Sipahutar (Universitas Negeri Medan, 2022)
This study aims to develop and test the feasibility of digital comic-based learning media and to examine its effect on student’s learning outcome in cell material. Learning media was developed according to the 4D development model of Thiagarajan which consisted of four stages, namely define, design, develop and disseminate. Media was validated by contentl expert, media expert, and learning expert. The suggestion from biology teacher and students of class XI MIA 2 SMA Negeri 2 Percut Sei Tuan were asked. The data of study were obtained through validation instruments, questionnaires, and cognitive test. Data were analyzed qualitatively and quantitatively. The result of the study showed that the developed comic media was considered very feasible by material expert (94,38%), media expert (89,34%), and learning expert (96,00%). Comic was considered very feasible too both by biology teachers (93.22%) and by students (92.38%). The results of the paired sample t-test on the pre-test and post-test score of 0.00 > 0.05 indicate that the post-test score is bigger than the pre-test score. The data showed that the result of cognitive test had increased significantly after using the developed digital comic media.